2014
DOI: 10.1016/j.hrthm.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance image intensity ratio, a normalized measure to enable interpatient comparability of left atrial fibrosis

Abstract: Background-The measurement of late gadolinium enhanced MRI (LGE-MRI) intensity in arbitrary units (au), limits the objectivity of thresholds for focal scar detection and inter-patient comparisons of scar burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
162
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 153 publications
(165 citation statements)
references
References 20 publications
2
162
0
1
Order By: Relevance
“…Images were processed off-line using QMass MR software (version 7.2; Leiden University Medical Center, Leiden, The Netherlands) as previously reported. 8 LA endocardial contours were manually drawn for 30 phases of the cardiac cycle in all slices covering the entire LA. The LA appendage was excluded.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Images were processed off-line using QMass MR software (version 7.2; Leiden University Medical Center, Leiden, The Netherlands) as previously reported. 8 LA endocardial contours were manually drawn for 30 phases of the cardiac cycle in all slices covering the entire LA. The LA appendage was excluded.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%
“…8,9 AF catheter ablation (CA) using pulmonary vein isolation by wide-area circumferential ablation has been used to decrease the burden of disease and improve AF-free survival. 10 Maintenance of sinus rhythm after ablation is associated with reverse remodeling, decreasing LA size and improving left ventricular (LV) function.…”
mentioning
confidence: 99%
“…[10][11][12] As such, there is an urgent need to develop new approaches for the treatment of complex atrial arrhythmias that incorporate understanding of contributions from the fibrotic remodelled tissue and are tailored to the individual patient. Given that late gadolinium-enhanced magnetic resonance imaging (LGE-MRI) can now be used to reconstruct each patient's unique fibrotic substrate, [13][14][15] the ultimate hope is that information extracted from such scans can be leveraged to guide powerful new ablation approaches that are custom-tailored to render the initiation and perpetuation of atrial re-entry in the given patient impossible. However, attempts to put this into practice have been greatly hindered by a dearth of understanding regarding how each individual's specific distribution of fibrotic tissue affects arrhythmia dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Although the atrial wall is thinner, native fibrosis and ablation scar can be identified using primarily threedimensional LGE techniques. 2,11 Findings from some studies have been interpreted to suggest that successful ablation of fibrotic regions, distant to the pulmonary veins (PVs), may help improve AF ablation success rates. 12 Similarly, atrial re-entrant circuits can be modelled in silico based on atrial scar location and can be used to inform ablation strategies.…”
mentioning
confidence: 99%